Pirolisis Katalitik Kayu Akasia (Acacia Mangium) Menjadi Bio-Oil Dengan Katalis Mo/ Lempung - Rahman, Aulia; Bahri, Syaiful; Khairat, Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Decreasing in fuel oil production capabilities and the increasing need for fuel oil will make Indonesia more addicted to fuel oil, thereby increasing the amoount of fuel imports. In Consequence, we need an innovation of energy conversion that does not rely on fossil resources, renewable and equal in value and function with fuel oil. One of that such innovation is the conversion of biomass derived from wood acacia (Acacia mangium) into bio-oil. Bio-oil can be produced through the pyrolysis process acacia (Acacia mangium) with catalyst Mo / Clay. The aims of this research is to produce bio-oil from acacia wood, determine the effect of pyrolysis temperature variations, the percentage and the amount of catalyst metal pengembanan Mo / clay and characterization of physical and chemical properties of bio-oil. Pyrolysis process carried out at the pyrolysis temperature variations 300oC, 320oC and 340oC, silinap 500 ml, biomass 50 grams with a size of -100 + 200 mesh sieve, the percentage variation of impregnation Mo metal to clay of 1%; 2% and 3%, as well as variations in the amount of catalyst Mo / clay of the biomass of 3%; 6% and 9%. The Results of this study is largest bio-oil yield in pyrolysis temperature of 320oC, the percentage of metal impregnation 2% and the use of catalysts Mo / clay 6% is 73,64%. Characterization of physical properties of bio-oil obtained in the form of density of 0,971 gr / ml, 2,079 cSt viscosity, acidity 58,369 mg NaOH / gram sample, the flash point 480C and the calorific value of 29,567 MJ / kg. While the characterization of the chemical properties of bio-oil using Gas Chromatography-Mass Spectroscopy (GCMS), several dominant chemical components such as acetic acid with a total area of 35,86%, 2-propanone with an area of 17,69%, 2-amino, 1-propanol with an area of 7,05%, propionic acid and an area of 6,20% and 1-hydroxy-2-butanone with an area of 4,12%.Keywords: bio-oil, catalyst Mo/Lempung, pyrolysis, Acacia mangium wood